Diverse roles of twitter in research evaluation: original tweets and retweets capture different types of engagements with scholarly articles - Maleki, Ashraf; Holmberg, Kim (Oxford University Press (OUP), 2026)
Altmetrics need to be more critically assessed in terms of the extent to which they reflect impact and quality of research compared to popularity or mere attention. Twitter (now rebranded as X) is a popular platform to, among other things, discuss and share scientific articles. Earlier altmetric studies have often focused on investigating whether the number of tweets mentioning scientific articles could be used as an indicator of scientific impact or attention, with results showing weak to moderate correlations with citation counts. But all tweets may not be equal, as original tweets and retweets may reflect different levels of engagement and impact. Using a dataset of over 330,000 PLOS publications, this study explores whether these two forms of Twitter activity correlate differently with traditional citation metrics and how these relationships vary across disciplines. The findings showed the correlation between citations and original tweets was consistently higher than that between citations and retweets and significant weak or moderate, but higher in Social Science and Humanities than in Natural Science, Engineering and Medicine fields. Also, including zero citation counts improved the correlation coefficients for original tweets, but reduced that of retweets. This indicates that original tweets may be more aligned with citation counts as an indicator of scholarly impact, whereas retweets might reflect broader dissemination and popularity. In conclusion, tweets and retweets are different altmetric indicators and should be considered as two different metrics and analysed separately.